Bridging cultures in the EFL classroom: the pedagogy of World Englishes in the Expanding Circle - Guerra, Luis (2015)
Applied linguists and language educators have been promoting lively debates over how globalization has been affecting the English language and how English has been influencing globalization. The increasing numbers of non-native speakers, the emergence of World Englishes, the use of English for intercultural communications, the intelligibility of standard and non-standard varieties of English, are just a few of the most talked about topics. Over the past decades, several applied linguists have reported on significant changes to be introduced in teaching the language. If we are to accept English as an international language of communication and incorporate these characteristics into the classroom, educators in the field of English language teaching will have to take on some responsibilities. According to Modiano (2001), in order to promote cultural equality, “a multiplicity of teaching practices, and a view of the language as belonging to a broad range of peoples and cultures, is the best that language instructors can do” (340). Moreover, Kirkpatrick (2007) suggests that “courses in World Englishes are becoming ever more popular and are seen, especially among ELT practitioners and professionals, as relevant for those who plan to become English language teachers” (1). Kirkpatrick believes that “the curriculum should comprise the cultures of the people using the language for cross-cultural communication rather than Anglo-American cultures” (3), thus questioning the appropriateness of the American and British native speaker models and their cultures. This presentation aims at discussing the advantages and possibilities of teaching native and non-native English varieties in the foreign language class. To do so, it presents some data which attempted to integrate linguistics and translation by analysing the features of Singapore English, Indian English and Australian English in terms of their phonological, morphological, lexical and syntactic levels.